A rare complication of a relatively common disease: periodic paralysis caused by thyrotoxicosis - Chanda, Abhishek; Mandal, Mainak; Sarkar, Suman; Roy, Nirmalya (International Journal of Advances in Medicine, 2023)
Thyrotoxic periodic paralysis is a sporadic form of hypo-kalemic periodic paralysis and it is most commonly presents as sudden onset weakness in the proximal muscles. It is a disorder most commonly seen in Asian men which is characterised by abrupt onset of hypo-kalemia and paralysis and it is primarily affects lower extremities and is secondary to thyrotoxicosis. It is due to an intracellular shift of potassium induced by thyroid hormone sensitisation of Na/K ATPase rather than depletion of total potassium. The absence of a family history, male predilection and, presentation in second to fourth decade of life and signs of thyrotoxicosis and sinus tachycardia help in the diagnosis of the disorder. The age of onset is later and corresponded with age of incidence of thyrotoxicosis. It is very essential to diagnose TPP early and treat appropriately.